Perdagangan Saham di Pasar Modal Syariah (Studi Kasus Bursa Efek Indonesia) - Gusniarti, Gusniarti (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2015)
The purpose of this research is to know how sharia’ application on stock trading at Islamic Capital Market not only primary market but also secondary market are good in Islamic perspective.We can use the question words of “what”, “what for” and “how” from Islamic perspective to identify that stock transaction in capital market allowed by Islam or not. The question of “what” is what is transaction object which traded in Islamic Capital Market. Are they suitable with shariah principle. The question of “what for” is what is the purpose of stock trading in capital market and the question word of “how” is how is the process of transaction in capital market especially secondary market. Are there prohibition activities there like speculation, short selling, netting, insider traiding, etc causing the price not reflection of the company fundamental.Stock transaction in Indonesian Stock Exchange as the place of research only can answer the question of “what”. This is related to transaction object in Islamic Capital Market. In this case, the shariah stock but another question cannot be answered well because still many prohibitions are done, no different from convensional capital market. In the fact, Islamic Capital Market only focuses on products. It has Islamic Index namely Jakarta Islamic Index filtering products is not prohibited in Islam.